2005
DOI: 10.1007/s11060-004-5672-5
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide-induced partial response in a patient with primary diffuse leptomeningeal gliomatosis

Abstract: Herein we describe the case of a patient with primary diffuse leptomeningeal gliomatosis (PDLG). After surgery and ventriculoperitoneal shunt placement, due to poor general conditions, the patient was not eligible for radiotherapy. For this reason we decided to start a systemic chemotherapy treatment with Temozolomide (150 mg/m2 per day for 5 days every 4 weeks). After three cycles a partial response was achieved with a clear improvement of general conditions. In our knowledge, this is the first time that PDLG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…Leptomeningeal dissemination of LGA is so rare that no treatment protocol for the situation is currently under evaluation. The ideal treatment is still under discussion 12,13 , but it has been suggested that chemotherapy instead of radiotherapy should be initially used 8 .…”
Section: Fig 8 Mri Sagittal Contrast-enhanced T1-weighted Image Of mentioning
confidence: 99%
“…Leptomeningeal dissemination of LGA is so rare that no treatment protocol for the situation is currently under evaluation. The ideal treatment is still under discussion 12,13 , but it has been suggested that chemotherapy instead of radiotherapy should be initially used 8 .…”
Section: Fig 8 Mri Sagittal Contrast-enhanced T1-weighted Image Of mentioning
confidence: 99%
“…Given that the recent multicenter phase 3 trial demonstrated a significant survival benefit from combining temozolomide and radiotherapy in the treatment of newly diagnosed glioblastoma [37], we opted for systemic treatment with temozolomide combined with radiotherapy in all of our patients. A recent report on a single case of PDLG has also suggested that temozolomide may be beneficial [26]. Survival time from onset of symptoms (74 weeks) was nearly twice as long as is typically seen in PDLG (41 weeks).…”
Section: Discussionmentioning
confidence: 93%
“…The development and use of MRI has increased this figure to 91% [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27]. Additionally, MRI of the spine has revealed abnormalities in 100% of the reported cases studied in this fashion [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27]. Clearly, the number of reported cases of PDLG has increased parallel to the development and use of MRI as a clinical adjuvant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations